2015
DOI: 10.1021/ja508766b
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Permeable Cyclic Peptides from Synthetic Libraries Inspired by Natural Products

Abstract: Drug design efforts are turning to a new generation of therapeutic targets, such as protein-protein interactions (PPIs), that had previously been considered "undruggable" by typical small molecules. There is an emerging view that accessing these targets will require molecules that are larger and more complex than typical small molecule drugs. Here, we present a methodology for the discovery of geometrically diverse, membrane permeable cyclic peptide scaffolds based on the synthesis and permeability screening o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
180
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 196 publications
(190 citation statements)
references
References 41 publications
7
180
0
3
Order By: Relevance
“…Nonetheless, the solution structures reveal that, in general, the NH hydrogen bond counts for cyclic peptides 1, 4, 5, 6, and 14 correlate well with cell permeability and EPSA, while hydrogen bonding among the −OH groups is prevalent throughout most of the structures and does not appear to correlate with permeability. These observations are consistent with other studies that challenge overall hydrogen bond count as a useful predictor of permeabilty, 2,4,22,44 especially when other factors are at play (such as flexibility and steric occlusion of polar groups).…”
Section: Journal Of Medicinal Chemistrysupporting
confidence: 92%
“…Nonetheless, the solution structures reveal that, in general, the NH hydrogen bond counts for cyclic peptides 1, 4, 5, 6, and 14 correlate well with cell permeability and EPSA, while hydrogen bonding among the −OH groups is prevalent throughout most of the structures and does not appear to correlate with permeability. These observations are consistent with other studies that challenge overall hydrogen bond count as a useful predictor of permeabilty, 2,4,22,44 especially when other factors are at play (such as flexibility and steric occlusion of polar groups).…”
Section: Journal Of Medicinal Chemistrysupporting
confidence: 92%
“…80 In fact, making cyclic peptides cell permeable by inclusion of N -methyl groups is an area of interest in the contemporary literature. 8183 Molecules 1 show promise as cell permeable molecules, even though they do not have tertiary amide N -methyl groups. We suggest this is because the favored conformers of 1 in solution orient their N-H vectors towards a central point, ie relatively insulated from the medium around the mimic.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, structural studies of cell-permeable peptides have suggested that steric occlusion of polar groups and internal hydrogen bonding can lead to increased permeability [39,40]. Recognizing that hydrogen bonding potential is heavily dependent on conformation, we explored whether structural tools that can experimentally probe the hydrogen bond network can also be used as biomarkers of peptide permeability.…”
Section: Discussionmentioning
confidence: 99%